Novel virtual hepatectomy is useful for evaluation of the portal territory for anatomical sectionectomy, segmentectomy, and hemihepatectomy. Issue 3 (March 2013) - Ariizumi, Shun‐ichi; Takahashi, Yutaka; Kotera, Yoshihito; Omori, Akiko; Yoneda, Godai; Mu, Han; Katagiri, Satoshi; Egawa, Hiroto; Yamamoto, Masakazu
Abstract Background The novel technique of virtual hepatectomy is useful for evaluation of the portal territory of the liver, since this software program includes functions for liver surgery planning. We evaluated the accuracy of virtual hepatectomy for anatomical hepatectomy. Methods Between 2010 and 2011, 92 patients with liver tumors underwent virtual hepatectomy preoperatively. The predicted liver volume was compared with the actual liver volume among patients who underwent anatomical sectionectomy, segmentectomy, and hemihepatectomy. Results Ninety of 92 patients underwent anatomical hepatectomy on the basis of virtual hepatectomy. According to the surgical procedure, the predicted liver resection volume showed a strong correlation with the actual liver volume in patients who underwent sectionectomy (r = 0.985, p < 0.0001, n = 44, median error rate 9 %), segmentectomy (r = 0.949, p < 0.0001, n = 17, median error rate 12 %), and hemihepatectomy (r = 0.967, p < 0.0001, n = 29, median error rate 7 %). Conclusions The novel technique of virtual hepatectomy is useful for evaluation of the portal territory for anatomical sectionectomy, segmentectomy, and hemihepatectomy.